2011
DOI: 10.1016/j.juro.2011.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Measured by Urine F2-Isoprostane Level is Associated With Prostate Cancer

Abstract: Background-Oxidative stress is implicated in prostate cancer (PCa) by several lines of evidence. We studied the relationship between the level of F2-Isoprostanes (F2IP), a validated biomarker of oxidative stress, and PCa and high-grade prostatic intraepithelial neoplasia (HGPIN).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 30 publications
3
53
0
Order By: Relevance
“…8, 9, 11 However, inconsistent with above studies, several cross-sectional studies collected blood samples after prostate cancers were diagnosed, and found that participants with prostate cancer had higher levels of F2-Isoprostane, malondialdehyde by thiobarbituric acid assay, and lower activities of superoxide dismutase and glutathione peroxidase than those without prostate cancer. 10, 12, 34, 35 Therefore, elevated oxidative stress in patients with prostate cancer in the above cross-sectional studies is likely to be the outcome of the prostate cancer or its comorbidities. High level of oxidative stress is unlikely considered to be an etiologic factor for prostate cancer incidence.…”
Section: Discussionmentioning
confidence: 99%
“…8, 9, 11 However, inconsistent with above studies, several cross-sectional studies collected blood samples after prostate cancers were diagnosed, and found that participants with prostate cancer had higher levels of F2-Isoprostane, malondialdehyde by thiobarbituric acid assay, and lower activities of superoxide dismutase and glutathione peroxidase than those without prostate cancer. 10, 12, 34, 35 Therefore, elevated oxidative stress in patients with prostate cancer in the above cross-sectional studies is likely to be the outcome of the prostate cancer or its comorbidities. High level of oxidative stress is unlikely considered to be an etiologic factor for prostate cancer incidence.…”
Section: Discussionmentioning
confidence: 99%
“…We included 238 adults with AMD and 390 age-and sex-matched controls without AMD who participated in a population-based cross-sectional study in Singapore (Singapore Chinese Eye Study, 2009-2011. AMD was graded from retinal photographs using the Wisconsin Age-Related Maculopathy Grading System.…”
Section: Methodsmentioning
confidence: 99%
“…Its circulating plasma levels have been associated with colon, prostate, and breast cancer [23], [24], [25], hence its association with malignant processes. To our knowledge, however, 8-Iso-PGF2 (8IP) has not been measured in BE or EAC tissue samples.…”
Section: Introductionmentioning
confidence: 99%